A contingent model for cell-free DNA testing to detect fetal aneuploidy after first trimester combined screening - Carmen Cotarelo-Pérez; Raluca Oancea-Ionescu; Eloy Asenjo-; Dolores Ortega-; Patricia Soler-Ruiz; Pluvio Coronado-Martín; María Fenollar-Cortés (Elsevier, 2019)
Objective: To assess the results of the first trimester combined test to design a prenatal protocol for the introduction of the cell-free fetal DNA test as a contingent screening model. Method: An observational retrospective study in 12,327 singleton pregnancies to analyze the results of the combined first trimester screening, the nuchal translucency ≥97.5 percentile, their cytogenetic results and birth outcomes. Results: A total of 533 (4.3%) pregnant women had a risk in combined first trimester screening above 1/300. In this group, sixty nine had an unbalanced karyotype. The abnormal/normal karyotype ratio was 1/28 in pregnant women with intermediate risk (1/51-1/300) for trisomy 21 and trisomy 18, 1/58 with intermediate risk just for trisomy 21 and 1/37 with intermediate risk just for trisomy 18. A 19.8% of the unbalanced karyotypes had chromosomal abnormalities other than trisomies 21, 18 and 13. Two false negatives cases at first trimester combined screening presented a nuchal translucency ≥ p97.5th. Conclusion: We propose the introduction of the cell-free fetal DNA test when the risk of first trimester combined screening is intermediate (1/51-1/300) and when nuchal translucency is ≥ p97.5th with a low risk in the combined screening. This policy would allow us to continue to detect uncommon chromosomal abnormalities. Keywords: Cell-free fetal DNA test, Chromosomal abnormalities, Aneuploidy, First trimester combined screening, Contingent model